Evaluation of flow characteristics in University Malaysia Pahang's sewerage system - Raziellia, Nor Saafri (2014)
Sanitary sewer systems which separately route sewerage from storm water and direct runoff are commonly applied in Malaysia. This is in accordance to weather conditions and high rainfall throughout the year. This type of sanitary sewer system is basically designed to accommodate the flow of wastewater from domestic and industrial waste rather than other sources. Problems may arise when the flow in the sewer system is not in accordance with specifications laid down in the Malaysian Standard MS 1228: 1990. This study aims to identify the flow characteristics in sewer systems through a study carried out during rainy and dry period, during the night and day period, during weekdays and weekends as well as determining the flow generated per capita and peak flow factor. In this study, flow characteristics of the sewer, systems are based on fieldwork conducted in the sewer system at the residential college in Universiti Malaysia Pahang, located near the mosque and student hostel block C15. The scope of the study covers the surrounding areas based on the population equivalent (PE) in the area. This study is to identify the characteristics of the sewage flow, done by using ISCO model 4250 flow meter with sensor area and velocity. Other than that, tipping bucket rain gauges were used to record rainfall data. The study also determine the characteristics of the flow in the sewer system which was carried out by calculating the total flow during the rainy and dry at the time to know the flow pattern. In addition, the amount of flow during night and day and also the amount of flow during weekdays and weekends are also calculated to examine the differences between the two periods. When there is no rain, the maximum flow rate is 4.908 l/s which is lower compared to when there is presence of rainfall which is 9.826 l/s. Besides that, there also a difference of maximum flow rate between holiday and working day where the maximum flow rate on working day is early in the morning compared to holiday. As a conclusion, the presence of rainfall and whether it is a working day or a holiday can influence the flow characteristics in the sewerage system.